Fundamentação do PRONAF como política pública: o comportamento e o impacto do programa no produto agropecuário de Minas Gerais no período 2013-2016 - Almeida, Thiago Rafael Corrêa de (2019)
This dissertation aims to evaluate the behavior and impact of PRONAF on the agricultural aggregate product in Minas Gerais in the period 2013-2016. The work was structured in three dimensions. The first perspective highlights the relevance of the research theme, addressing, on the one hand, issues related to the importance and weight of farming and family agriculture as well as presenting a diagnosis of aspects linked to inequality and vulnerability in the field and, on the other hand, discussion on the issue of agricultural credit for development. This dimension also tangentially addresses theoretical and empirical elements that help to understand the reasons for the study. The second perspective deals with the program (PRONAF) which attempts to partially modify the situation of family farmers. It addresses elements linked to the creation (genesis), conception, operation of the program and its problems in an analysis articulated with the public policy fundamentals (normative-analytical and organizational-managerial components) of the program. Finally, the third dimension provides an exploratory analysis of the data and the panel data methodology used to verify the impact of the program on the value added of agriculture in Minas Gerais and presents the main results.